2014
DOI: 10.1021/mz5003068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mechanochemical Chain Scission Rates for Linear versus Three-Arm Star Polymers in Strong Acoustic Fields

Abstract: The effect of star versus linear polymer architecture on the rates of mechanochemically induced bond scission has been explored. We determined rate constants for chain scission of parent linear and star polymers, from which daughter fragments were cleanly resolved. These studies confirm a mechanistic interpretation of star polymer chain scission that is governed by the spanning rather than total molecular weight. We further demonstrate the preserved rate of site-selective mechanophore activation across two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 47 publications
4
109
0
4
Order By: Relevance
“…28 Indeed, GPC chromatogram RI traces recorded during the course of PMA-2 's irradiation with ultrasound reveal the expected decrease of the initial high molecular weight peak (12.6 min) and the formation of two new fragments, one at 2/3 (12.9 min) and one at 1/3 (13.7 min) of the initial molecular weight indicating scission of one polymer arm (Fig. 4a).…”
Section: Resultsmentioning
confidence: 91%
“…28 Indeed, GPC chromatogram RI traces recorded during the course of PMA-2 's irradiation with ultrasound reveal the expected decrease of the initial high molecular weight peak (12.6 min) and the formation of two new fragments, one at 2/3 (12.9 min) and one at 1/3 (13.7 min) of the initial molecular weight indicating scission of one polymer arm (Fig. 4a).…”
Section: Resultsmentioning
confidence: 91%
“…The central principle we sought to confirm was that in star polymers, the rates of mechanochemical activation are governed by the molecular weight of each arm ( M arm ) rather than the total molecular weight ( M total ) . We investigated by synthesizing and sonicating a series of three‐arm star poly(methyl acrylate)s and a complementary set of linear poly(methyl acrylate)s and monitoring the decrease in concentration of the parent polymer (Figure and Table ) . The results confirmed that the spanning molecular weight – that is, the molecular weight across two of the three arms in star polymers – is the factor that determines the rate of activation, consistent with existing theories.…”
Section: Fundamental Polymer Mechanochemistrymentioning
confidence: 70%
“…This concept was further extended to examine the rates of site‐specific mechanophore activation as a function of polymer topology. By incorporating an anthracene‐maleimide Diels–Alder adduct mechanophore near the core of linear and star polymers of the same M arm , nearly identical rates of mechanophore activation were observed, both by GPC and fluorescence spectroscopy (Figure and Table ) . The combination of these studies, therefore, provided quantitative guidelines for either moderating or augmenting the mechanochemical reaction rates of macromolecules by altering their overall topology.…”
Section: Fundamental Polymer Mechanochemistrymentioning
confidence: 84%
“…[23] In phasenseparierten Systemen findet FRET hauptsächlich im Grenzflächenbereich statt und wird von der Domänengrçße und der Exzitonendiffusionslänge bestimmt. Folglich werden die beobachteten MIFCs nicht von den kristallinen VE-CP-Komponenten bestimmt, was eine Erweiterung der bisherigen MIFC-Prinzipien darstellt, die meist durch die Abwechslung molekularer Packungsanordnungen in kristallinen oder flüssigkristallinen Systemen, chemischen Reaktionen und Isomerisierung bestimmt wurde.…”
Section: Angewandte Chemieunclassified